THE STRUCTURAL RELATIONSHIP BETWEEN LEADERSHIP EFFECTIVENESS, WORK ENVIRONMENT, AND OPERATIONAL PERFORMANCE OF POLICE OFFICERS - Vita Mayastinasari; Bayu Suseno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Leadership effectiveness and the quality of the work environment are central determinants of the operational performance of police officers. This literature review synthesizes empirical and conceptual research published between 2015 and 2025 to clarify how leadership behaviors and organizational work conditions interact to shape operational outcomes such as response times, arrest accuracy, procedural justice adherence, use of force incidents, and overall task performance. Drawing on a purposive sample of peer reviewed studies, program evaluations, and practitioner reports, the review integrates findings across quantitative surveys, qualitative case studies, and implementation evaluations. Evidence indicates that transformational, servant, and coaching leadership styles increase officer motivation, psychological safety, and discretionary effort which in turn improve operational performance measures when work environment factors such as role clarity, adequate resources, supervisory support, and fair policies are present (Mulyana, 2024; Damayanti, 2025). Conversely, high job stress, bureaucratic rigidity, unclear performance criteria, and resource scarcity attenuate leadership effects and can produce negative operational outcomes (Sihombing et al., 2022; Karimullah, 2024). The review highlights mediating mechanisms perceived organizational support, job satisfaction, and psychological safety and moderating conditions such as organizational culture, external oversight, and workload. Practical recommendations include investing in leadership development with explicit coaching skills, improving work environment design through resource allocation and procedural clarity, embedding continuous feedback systems, and aligning performance metrics with community oriented policing goals. The paper concludes with a research agenda that calls for longitudinal and multi site evaluations to establish causal pathways between leadership, environment, and operational performance in policing contexts. Keywords: leadership effectiveness, work environment, operational performance, policing